Legal professions work, structure and organization - Van Hoy, Jerry (Amsterdam ; London : JAI, 2001)
During recent decades legal professions have changed dramatically. Legal work has become more specialized, women have entered legal professions in large numbers, and the number of nonwhite legal practitioners has increased. Equally important as the demographic changes among legal professionals, have been movements in several countries to make legal practice more responsive to competitive markets for services - both nationally and globally. This volume introduces a collection of research articles that explore the important changes among legal practitioners in the US, England, Germany and Canada. The articles are organized around three general themes: changes in the structure and organization of legal professions and legal practices (in the US, England and Germany); legal culture, professional time and job satisfaction (in the US and England); and the changing nature of legal work practices in various fields of law. The volume addresses many of the newest and most exciting themes in the sociology of law, including the global law firm, the dilemma of part-time employment for legal professionals, the sociolegal construction of time, and the unique dynamics of legal practices in different fields of law.
Part one: Change in the structure of legal professions -- The changing patterns of career mobility in the legal profeesion: a log-linear analysis of Chicago lawyers (1975 and 1995) / Harris H. Kim -- The State-lawyer relationship in England and Wales / Gerard Hanlon -- Mergers, mergers everywhere: constructing the global law firm in Germany / Susanne Lace -- Part two: Legal culture, professional time, and job satisfaction -- The symbolic meaning of professional time / Cynthia Fuchs Epstein and Carroll Seron -- Time, legal culture and legal process / Robert Dingwall, William L.F. Felstiner and Tom Durkin -- Explaining why lawyers want to leave the practice of law / Jean E. Wallace -- Part three: Lawyers and their work -- "We live on the edge of extinction all the time:" entrepreneurs, innovation and the plaintiffs' bar in the wake of tort reform / Stephen Daniels and Joanne Martin -- Career activism by lawyers: consequences for the person, the legal profession, and social movements / Lynn C. Jones -- Lawyering in an age of popular politics: plea bargaining, legal practice and the structure of the Boston Bar, 1800-1860 / Mary E. Vogel -- Perceptions of good and bad judging: an analysis of the Illinois judicial development project / Katherine Cermak and Richard Block.
Includes bibliographical references.
Description based on print version record.
Keywords: Lawyers; Practice of law; Sociological jurisprudence; Legal profession -- General; United Kingdom, Great Britain; Social Science -- Criminology; Electronic books